2001
DOI: 10.1080/17461390100071203
|View full text |Cite
|
Sign up to set email alerts
|

Activation and torque deficits in ACL‐reconstructed patients 4 months post‐operative

Abstract: This study compares knee extension and flexion torques and electromyographic (EMG) activity of normal and anterior cruciate ligament (ACL)-reconstructed knees during maximal unilateral isometric and isokinetic tests performed 4-5 months after ACL reconstruction. The subjects consisted of 3 age-and activity-matched groups of 6 subjects: a healthy control group (Ctrl) and 2 groups of patients, with Kenneth-Jones technique using autologous patellar-ligament graft (KJ group) and autologous graft from the semitendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…These differences may be related to the injury, since control of movement during acceleration could be affected, and the ability to attain the specific isokinetic velocity at a given range of motion may also be impaired. 33 Moreover, the TAV 3D , which provides a qualitative evaluation, demonstrated that the control group was able to maintain higher torques at higher velocities. In flexor and extensor muscles, the range of motion and the distribution of the torque during the range can change in post ACLR patients.…”
Section: Table 3 Peak Torque and Of Peak Torque At Different Velocitiesmentioning
confidence: 97%
“…These differences may be related to the injury, since control of movement during acceleration could be affected, and the ability to attain the specific isokinetic velocity at a given range of motion may also be impaired. 33 Moreover, the TAV 3D , which provides a qualitative evaluation, demonstrated that the control group was able to maintain higher torques at higher velocities. In flexor and extensor muscles, the range of motion and the distribution of the torque during the range can change in post ACLR patients.…”
Section: Table 3 Peak Torque and Of Peak Torque At Different Velocitiesmentioning
confidence: 97%